Collaborative project work development in a virtual environment with low-intermediate undergraduate colombian students (2014)
This paper reports on an exploratory, descriptive, and interpretive study in which the roles of discussion boards, the students, the teacher, and the monitors were explored as they constructed a collaborative class project in a virtual environment. This research was conducted in the virtual program of a Colombian public university. Data were gathered through a questionnaire, recordings of conversations through Skype, and artifacts or samples of students’ participation in the discussion boards. The analysis of the data followed the principles of grounded theory. The main findings suggest that as they were doing project work in a virtual environment, students played the role of team workers, the teacher and monitors played shared roles, and the discussion boards served as a facilitating tool.En este documento se presenta un estudio exploratorio, descriptivo e interpretativo, en el que se analiza el papel de los foros de discusión, de los estudiantes, del profesor y de los monitores mientras construían un proyecto colaborativo en un ambiente virtual. La investigación se llevó a cabo en un programa virtual de una universidad pública en Colombia. Los datos se recolectaron a través de un cuestionario, grabaciones de conversaciones por medio del programa Skype y ejemplos de las participaciones de los estudiantes en los foros de discusión; y se analizaron siguiendo los principios de la teoría fundamentada. Los principales resultados indican que mientras se realizaba el proyecto colaborativo, los estudiantes cumplieron el papel de trabajadores en equipo; el profesor y los monitores adoptaron papeles compartidos y los foros de discusión actuaron como herramienta facilitadora.